2016
DOI: 10.1111/are.13153
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic profile of Antiviral Mx gene and its role in innate immunity in Mrigal,Cirrhinus mrigala(Hamilton 1822)

Abstract: The aim of this study was to determine the ontogeny of antiviral Mx gene expression in different stages of development of Cirrhinus mrigala (mrigal). For this purpose, three experiments were designed; in the first experiment, Mx expression was observed in eggs, milt, poly I:C treated twitching stage and control twitching stage, and the Mx expression was maximum in eggs. In the second experiment, upregulation of Mx transcript was studied in hatchling stages of mrigal after poly I:C induction by bath treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The existence of Mx protein in calta was witnnessed with qPCR and immunostaining of the blood cells of catla. The Mx transcript was observed by western blotting of poly I:C stimulated blood cells with a band at 72 kDa in L. catla and C. mrigala (Roy et al, 2017). Similarly, an assumed Mx protein of approximately 76 kDa was reported across the organs of poly I: C treated Atlantic halibut and Atlantic salmon parr (Das et al, 2007;Lockhart et al, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…The existence of Mx protein in calta was witnnessed with qPCR and immunostaining of the blood cells of catla. The Mx transcript was observed by western blotting of poly I:C stimulated blood cells with a band at 72 kDa in L. catla and C. mrigala (Roy et al, 2017). Similarly, an assumed Mx protein of approximately 76 kDa was reported across the organs of poly I: C treated Atlantic halibut and Atlantic salmon parr (Das et al, 2007;Lockhart et al, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…Poly I:C (mimic of RNA virus) has been widely used to induce the expression of antiviral genes in fish [9,10]. It has been reported that Mrigal carp (Cirrhinus mrigala), bathed for 2 hr in water containing Poly I:C, expressed increased levels of MX transcripts [11]. While Poly I:C is widely used as a TLR3/TRIF pathway agonist [12], it can also induce a type I IFN response through the MDA5/NF-kB signaling pathway in miiuy croaker (Miichthys miiuy) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly in rainbow trout, maternal transfer of IgM and complement components has been studied by 32 . The ontogenic study of Mx gene expression at diffrent developmental stages have been reported in C. mrigala 33,34 . In fishes, the Mx gene is induced by Type-I Interferon, the main cytokine mediating the innate immune antiviral function.…”
Section: Introductionmentioning
confidence: 99%